Μ-Synthesis Controller Design for Seismic Alleviation of Structures with Parametric Uncertainties. Issue 4 (December 2015) - Gudarzi, Mohammad
The purpose of this paper is to apply robust μ-synthesis output-feedback controller design for seismic alleviation of multi-structural buildings with parametric uncertainties and to tackle the instabilities and performance declines due to these uncertainties. To this aim, a general lumped-mass tree-building model of a shear-frame multi-structure with horizontal movements is developed, first. Then, an output-feedback controller based on the theory of structured singular value is designed for the main structure that not only alleviates the earthquake excitation but also guarantees the stability of the closed-loop system. Finally, to investigate the effect of the designed controller on the main and neighbouring structures, numerical simulations using historically recorded ground accelerations are carried out, where certain percentages of uncertainties are added to the multi-structure's parameters and the results are compared to those for passive structures and the results are discussed.